Transpersonal Leadership in Action : how to lead beyond the ego - Enright, Duncan (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"How can leaders promote diversity, equality and inclusion? What does it mean to let go of leadership? How do learning, feedback and coaching help us to be better leaders? Following the success of Leading Beyond the Ego, this book shows how to apply Transpersonal Leadership - practiced leaders who are radical, ethical, authentic and act beyond their own interests to create high-performing organisations - in a wide range of leadership contexts. It considers the attributes of transpersonal leaders and how they can transform organisations by building strong, collaborative relationships and a caring, sustainable and performance enhancing environment. This book builds on Leading Beyond the Ego to provide real-life examples of Transpersonal Leadership in action. Shining a light on the way forward for senior leaders, HR and talent professionals, it covers: The characteristics of transpersonal leaders such as purpose, ethics, and adult development and the value they bring The impact of transpersonal leaders on global organisations, during digital transformation and change and through crises Case studies of transpersonal leadership in different contexts including in India and East Asia, when leading remotely, among politicians, along with a guide for HR professionals. A way to understand leadership development in the context of adult development Transpersonal Leadership in Action is essential reading for senior leaders, HR professionals, and those responsible for leader and organisational development"--
Includes bibliographical references and index.
Keywords: Leadership; Executive coaching